EPIDEMIOLOGICAL AND CLINICAL CHARACTERISTICS OF 2019 NOVEL CORONA VIRUS: A REVIEW - SRIKALA, T SAI LAKSHMI; KUMAR, T PRAVEEN (Innovare Journal of Sciences, 2021)
Middle East Respiratory Syndrome (MERS), having a high demise rate, which radiate from the Middle East. Novel Coronavirus is the causative living being for MERS and (2019-nCoV) was recognized infection by Chinese experts on January 7. On December 31, 2019, the WHO China Country Office was educated regarding instances of pneumonia of obscure etiologic (obscure reason) identified in Wuhan City, Hubei Province of China. Besides, MERS-CoV first found in dromedary camels and in bats, people. Proof recommends that animals are acting as host for MERS-CoV and transmitting the malady to people. Till the finish of November 2019, an aggregate of 2494 lab instances of MERS, were recorded which incorporates 858 deaths around the world. At present, no drug or immunization is accessible for MERS. As we knew that prevention is better than cure, taking precautions before attacking of the disease is the best way of preventing disease. In this study, we discussed about the pathological aspects, treatment strategies, and precautions of the disease.